Formulation and evaluation of bi-layer floating tablets of ziprasidone HCl and trihexyphenidyl HCl - Sathis Kumar Dinakaran; Santhos Kumar; David Banji; Harani Avasarala; Venkateshwar Rao (Universidade de São Paulo, 2011)
The purpose of this research study was to establish ziprasidone HCl NR 40 mg and trihexyphenidyl HCl SR 4mg in the form of bi-layer sustained release floating tablets. The tablets were prepared using sodium HPMC K4M / HPMC K15M as bio-adhesive polymers and sodium bicarbonate acting as a floating layer. Tablets were evaluated based on different parameters such as thickness, hardness, friability, weight variation, in vitro dissolution studies, content of active ingredient and IR studies. The physico-chemical properties of the finished product complied with the specifications. In vitro release from the formulation was studied as per the USP XXIII dissolution procedure. The formulations gave a normal release effect followed by sustained release for 12 h which indicates bimodal release of ziprasidone HCl from the matrix tablets. The data obtained was fitted to Peppas models. Analysis of n values of the Korsmeyer equation indicated that the drug release involved non-diffusional mechanisms. By the present study, it can be concluded that bi-layer tablets of ziprasidone HCl and trihexyphenidyl HCl will be a useful strategy for extending the metabolism and improving the bioavailability of Ziprasidone HCl and Trihexyphenidyl HCl. O propósito deste trabalho foi preparar ziprasidona. HCl NR 40 mg e triexifenidila.HCl SR 4 mg na forma de comprimidos efervescentes bicamada de liberação controlada. Os comprimidos foram preparados utilizando HPMC K4M / HPMC K15M sódico como polímero bioadesivo e bicarbonato como camada efervescente. Os comprimidos foram avaliados quanto a diferentes parâmetros, como espessura, dureza, friabilidade, variação de peso, dissolução in vitro, conteúdo do ingrediente ativo e estudos de IV. As propriedades físico-químicas dos produtos finais cumprem as especificações. A liberação in vitro da formulação foi estudada de acordo com o procedimento de dissolução da USP XXIII. As formulações resultaram em liberação normal, seguida por liberação controlada por 12 h, o que indica a liberação bimodal de cloridrato de ziprasidona dos comprimidos matriz. Os dados obtidos se adequaram aos modelos de Peppas. A análise de valores de n da equação de Korsmeyer indicou que a liberação do fármaco envolveu mecanismos não difusionais. Por este estudo, pode-se concluir que os comprimidos bicamada de ziprasidona.HCl e de triexifenidila.HCl serão um bom caminho para estender o metabolismo e para melhorar a biodisponibilidade de ziprasidona.HCl e de triexifenidila.HCl.